Upcoming: Assessing the Potential Challenges of Paid LLMs and Inequities in Language Classrooms - Aditi Jhaveri (Journal of the Scholarship of Teaching and Learning)
This essay examines the potential impact of paid-for or premium language models, where some students may be able to afford advanced models generating superior outputs while others could face inequities due to financial constraints. It explores how this dynamic can exacerbate the digital divide, challenge traditional as well as more recent assessment methods in language education, and discusses strategies that hold promise in navigating these complexities in the era of Generative AI within the context of higher education.